Current transients for the hydrogen evolution reaction at high overpotentials on silver electrodes in acid solutions: Experiments and modelling - Ruderman, Andres (2013)
The hydrogen evolution reaction has been investigated on Ag(1 0 0) by potentiostatic current transientsat high overpotentials (- > 0.7 V) in acidic solutions. The reaction proceeds via the Volmer-Heyrovskymechanism, simultaneously coupled with desorption of sulphate/disulphate anions. Volmer is the ratedetermined step, although the Heyrovsky reaction is only slightly faster. The kinetic parameters havebeen obtained under various conditions of pH and concentration of anions. A catalytic effect due to thepresence of anions has been observed. © 2013 Elsevier Ltd. All rights reserved.